PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT SURYA BUMI SENTOSA - Junesco, Vannes; Alam, Iskandar Ali (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
This research aims to determine the effect of compensation and work motivation on employee performance at PT. Surya Bumi Sentosa. This research is a population study, because the total number of employees is 40 people. The analysis technique used in this research is quantitative data analysis, so to make it easier for researchers to carry out research, researchers carry out analysis using the SPSS 25 program with multiple linear test analysis tools, coefficient of determination test, t test and F test. Based on the results of data analysis and discussion, it is concluded that compensation and work motivation, both partially and jointly, have a significant effect on employee performance at PT. Surya Bumi Sentosa.